Encyclopedia of Psychology, Vol. 3. 2000
DOI: 10.1037/10518-019
|View full text |Cite
|
Sign up to set email alerts
|

Divorce.

Abstract: processes such as attachment mechanisms is not known at this time.An important neurological question is the relationship between dissociative processes and other neurological disorders. especially temporal lobe epilepsy (see Zahn. Moraga. & Ray, 1997 for a review). While the appearance of dissociative phenomena among individuals with temporal lobe epilepsy has been well documented, the data do not support a seizure disorder model as a primary mechanism for dissociation. Thus, although it is clear that individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our analyses indicate the importance of three categories of paternal and family characteristics in predicting patterns of involvement: paternal characteristics, household configuration, and family relationships. The consideration of these variables represents an important extension of previous research on the correlates and predictors of paternal involvement, which has focused almost exclusively on characteristics of the child and father (Furstenberg & Harris, 1993;Lerman, 1993;Seltzer, 1991; but see Hetherington & Stanley Hagan, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses indicate the importance of three categories of paternal and family characteristics in predicting patterns of involvement: paternal characteristics, household configuration, and family relationships. The consideration of these variables represents an important extension of previous research on the correlates and predictors of paternal involvement, which has focused almost exclusively on characteristics of the child and father (Furstenberg & Harris, 1993;Lerman, 1993;Seltzer, 1991; but see Hetherington & Stanley Hagan, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Poverty may increase the stress in such families to manage the daily needs and health care. Such stress can cause many health problems such as immune deficiency, depression and anxiety, which are the risk factors for obstetric morbidity (Hetherington & Stanley-Hagan, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As society is becoming increasingly diverse regarding family structures, it is important for there to be further research conducted on the relations between father and child -this is clear as there have been studies that show the detrimental effects of father absenteeism on child development. It has been found that not only are behavioural issues at school more likely to occur in children who live without their fathers [10], but these children are also more likely to perform lower on academic tests than children who live with their fathers [11]. These findings make it clear that fathers must be encouraged to be involved in their children's lives and that more awareness should be raised of the importance that fathers play in the lives of their children.…”
Section: Introductionmentioning
confidence: 99%